Temperature effects on stripping performance of superpave design mix / Ekarizan Shaffie, Juraidah Ahmad and Mohd Yusof Abdul Rahman - Shaffie, Ekarizan; Ahmad, Juraidah; Abdul Rahman, Mohd Yusof (Research Management Institute (RMI), 2008)
Climatic factor such as temperature and moisture has profound effect on the durability of hot mix asphalt pavements. Couple with high traffic loads/stresses made stripping of pavement materials inevitable. Thus, it has become necessary to improve the efficiency of the design of hot mix asphalt (HMA) for better performance and safe riding comfort. This study investigates and discusses the findings on the stripping performance of dense graded Superpave mixes using two types of binder, Penetration Grade (PEN) 80-100 (unmodified) and PEN 80-100 with rubber-polymer (modified binder). The HMA preparation follows the Superpave mix design AASHTO TP4 procedures. The optimum percentage of rubber crumb and Ethylene-Vinyl-Acetate (EVA) polymer was selected based on the previous research. Indirect tensile resilient modulus test was used to evaluate the stripping performance in both unmodified and rubber-polymer modified mixes. This study also documents the effect of different temperatures on tensile strength ratio (TSR) and resilient modulus ratio (RMR) on the HMA mixtures. Statistical analysis performed indicates that rubber-polymer modified binder mix (RPMM) significantly improved the resistance of the HMA mix to moisture damage compared to unmodified mix (UnM).